GROWTH RESPONSE OF JUVENILE GRASS CARP (CTENOPHARYNGODON IDELLA) FED ISOCALORIC DIETS WITH VARIABLE PROTEIN LEVELS - R. Ghazala; A. B. Tabinda; A. Yasar (Journal of Animal and Plant Sciences, 2011)
Sixty days feeding experiment was conducted on grass carp fry fed isocaloric diets with variable protein levels in order to evaluate its growth response. Different diet ingredients were analyzed for % age protein, % age fat, % age ash, % fiber, % age moisture contents and energy. Five isoenergetic (17.91 ± 0.02 Kg MJ-1) and isolipidic (8.56 ± 0.09 g) diets with varying protein levels PL1 (20%), PL2 (25%), PL3 (30%), PL4 (35%) and PL5 (40%) were formulated, analyzed and fed to triplicate groups of fish fry each group comprised of 10 fish (average weight 0.57 ± 0.001g fish-1). Experimental design was a completely randomized design. Highest mean weight gain, average daily growth, final weight gain, specific growth rate but lowest feed conversion ratio were observed (P<0.05) in fish fed diet PL5 (40% protein level diet). Whereas significantly lowest mean weight gain, average daily growth, percent weight gain, specific growth rate but highest feed conversion ratio (P<0.05) were observed for PL1 (20% protein level diet). Average temperature (29.66–30.0 ºC), pH (8.32–8.55), dissolved oxygen (6.31-6.60 mg/L) were within the optimum range throughout the experiment and did not significantly differ among different treatments (P<0.05). Present study revealed that forty percent protein level is best and economical for rearing grass carp fry.
Keywords: Ctenopharyngodon idella fry; Nutrition; Protein; Dietary requirement; Growth.